12.9-grade wind power bolt material and preparation method and application thereof
Patent Information
- Application Number
- CN202511060840.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-07-30
AI Technical Summary
本发明的目的在于提供一种12.9级风电螺栓材料及其制备方法、应用,通过重新设计成分及优化热处理工艺,生产出机械性能满足12.9级高强度、M42-M72大规格的风电螺栓材料,以解决42CrMo难满足M42-M72大规格12.9级风电螺栓性能的问题
[0021]1、本发明的12.9级风电螺栓材料,通过添加提升淬透性的元素Mn、Cr、Mo,并将其含量分别控制为Mn:0.52-0.58%、Cr:1.10-1.15%、Mo:0.22-0.28%,保证材料的淬透性;添加微合金元素V、Nb,可使晶粒度细化,可提高材料的综合性能;添加元素Ni,可提高钢淬透性,可以保证材料低温冲击韧性。
Smart Images

Figure CN120666249B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fastener steel technology, and in particular relates to a 12.9 grade wind power bolt material, its preparation method, and its application. Background Technology
[0002] Wind power is an important renewable energy source. In 2024, my country's cumulative installed wind power capacity exceeded 500GW, with a target of 3000GW by 2060, indicating that wind power has entered a stage of rapid development. Bolts are an important component of wind turbine generators, primarily serving a connecting and fastening function, including tower bolts, blade bolts, and ground anchor bolts. 42CrMo is a typical alloy structural steel; after quenching and tempering, it can achieve good comprehensive mechanical properties and is widely used in manufacturing 10.9 and 12.9 grade high-strength bolts. However, the critical hardening diameter of 42CrMo is around φ40mm, making it difficult to meet the performance requirements of large-size bolts from M42 to M72.
[0003] In view of this, the present invention is hereby proposed. Summary of the Invention
[0004] Currently, the critical hardenability diameter of 42CrMo used is around φ40mm. With the increase in wind turbine capacity, the use of bolts also increases, and this material is insufficient to meet the performance requirements of large-size M42-M72 bolts. The purpose of this invention is to provide a 12.9 grade wind turbine bolt material, its preparation method, and its applications. By redesigning the composition and optimizing the heat treatment process, a wind turbine bolt material with the mechanical properties of 12.9 grade high strength and suitable for large sizes of M42-M72 is produced, thus solving the problem that 42CrMo cannot meet the performance requirements of 12.9 grade wind turbine bolts with large sizes of M42-M72.
[0005] To achieve the above objectives, the present invention adopts the following technical solution:
[0006] In a first aspect, the present invention provides a 12.9 grade wind turbine bolt material, wherein the 12.9 grade wind turbine bolt material comprises, by mass percentage, the following elemental composition: C: 0.38-0.45%, Si: 0.20-0.30%, Mn: 0.52-0.58%, P: ≤0.010%, S: ≤0.005%, Cr: 1.10-1.15%, Mo: 0.22-0.28%, Cu: ≤0.10%, Ni: 0.30-0.40%, V: 0.10-0.15%, Nb: 0.02-0.03%, Al: 0.02-0.03%, with the remainder being Fe and unavoidable impurities.
[0007] In a second aspect, the present invention provides a method for preparing the 12.9 grade wind turbine bolt material described in the first aspect, wherein the round steel material prepared by converter, LF refining, RH vacuum degassing, continuous casting and rolling processes is subjected to heat treatment tempering and quenching, wherein the rolling process adopts a controlled rolling and controlled cooling process, wherein the final rolling temperature during controlled rolling is not less than 810°C, and the cooling rate during controlled cooling is 0.5-0.8°C / s.
[0008] Furthermore, the final rolling temperature is 810-840℃.
[0009] Furthermore, the final rolling temperature is controlled by water cooling;
[0010] And / or, the cooling rate is controlled by a heat insulation cover during controlled cooling.
[0011] Furthermore, the continuous casting employs a light reduction technique.
[0012] Furthermore, the temperature of the continuously cast billet before rolling is 1180–1220°C.
[0013] Furthermore, the quenching adopts a quenching temperature of not less than 880℃ and a water cooling process;
[0014] And / or, the tempering adopts a tempering temperature not exceeding 630°C and a water cooling process.
[0015] Furthermore, the quenching temperature is 880-900℃;
[0016] And / or, the tempering temperature is 570-630℃.
[0017] Further, the quenching temperature is 880℃, and the tempering temperature is 570~630℃; further, the quenching temperature is 880℃, and the tempering temperature is 630℃.
[0018] And / or, the quenching temperature is 900℃, and the tempering temperature is 600~630℃.
[0019] A third aspect of the present invention provides the application of the 12.9 grade wind turbine bolt material described in the first aspect or the 12.9 grade wind turbine bolt material prepared by the preparation method of the second aspect, wherein the 12.9 grade wind turbine bolt material is applied to the preparation of M42-M72 specification, 12.9 grade high strength wind turbine bolts.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] 1. The 12.9 grade wind turbine bolt material of the present invention improves hardenability by adding Mn, Cr, and Mo, and controlling their contents to Mn: 0.52-0.58%, Cr: 1.10-1.15%, and Mo: 0.22-0.28%, respectively. The addition of microalloying elements V and Nb refines the grain size and improves the overall performance of the material. The addition of element Ni improves the hardenability of steel and ensures the low-temperature impact toughness of the material.
[0022] 2. The preparation method of the 12.9 grade wind turbine bolt material of the present invention optimizes the heat treatment process, including controlled rolling and controlled cooling process during rolling. The final rolling temperature during controlled rolling is not less than 810℃, and the cooling rate during controlled cooling is 0.5-0.8℃ / s, so as to obtain a uniform and stable ferrite F and pearlite P structure, which is more conducive to the improvement of subsequent quenching and tempering heat treatment performance. Furthermore, by controlling the quenching and tempering heat treatment temperature during heat treatment, the mechanical properties of the material are improved, so as to obtain a material that meets the performance requirements of 12.9 grade wind turbine bolts.
[0023] 3. The 12.9 grade wind turbine bolt material of the present invention can be used to produce wind turbine bolts with high strength of 12.9 grade and large size of M42-M72, so as to solve the problem that 42CrMo is difficult to meet the performance of 12.9 grade wind turbine bolts with large size of M42-M72. Attached Figure Description
[0024] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0025] Figure 1 The metallographic structure of the material after light rolling provided in Embodiment 5 of the present invention Figure 1 ;
[0026] Figure 2 Metallographic structure of the tempered material provided in Embodiment 5 of the present invention Figure 2 ;
[0027] Figure 3 This is a low-magnification microstructure diagram of the material after light rolling provided in Embodiment 5 of the present invention;
[0028] Figure 4 This is a low-magnification microstructure diagram of the material after rolling without using light pressure, provided in Embodiment 9 of the present invention. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Those skilled in the art should understand that the embodiments described are merely illustrative of the invention and should not be considered as specific limitations thereof. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention. Process parameters not specifically specified in the following embodiments are generally performed under conventional conditions.
[0030] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0031] According to a first aspect of the present invention, the present invention provides a 12.9 grade wind turbine bolt material, the 12.9 grade wind turbine bolt material comprising, by mass percentage, the following elemental composition: C: 0.38-0.45%, Si: 0.20-0.30%, Mn: 0.52-0.58%, P: ≤0.010%, S: ≤0.005%, Cr: 1.10-1.15%, Mo: 0.22-0.28%, Cu: ≤0.10%, Ni: 0.30-0.40%, V: 0.10-0.15%, Nb: 0.02-0.03%, Al: 0.02-0.03%, with the remainder being Fe and unavoidable impurities.
[0032] In this invention, since the critical hardenability diameter of the existing 42CrMo is about φ40mm, and the chemical composition directly affects the performance of the material product, the inventors mainly considered the strength and low-temperature impact performance of the material after heat treatment when designing the composition. Therefore, (1) the elements Mn, Cr and Mo are added to improve the hardenability of the wind power bolt material, and the contents of Mn, Cr and Mo are controlled to Mn: 0.52-0.58%, Cr: 1.10-1.15% and Mo: 0.22-0.28% respectively to ensure the hardenability of the material; (2) the micro-alloying elements V and Nb are added to refine the grain size and improve the comprehensive performance of the material; (3) the element Ni is added to improve the hardenability of the steel and ensure the low-temperature impact toughness of the material. Therefore, in the 12.9 grade wind turbine bolt material of this invention, the C content, calculated by mass percentage, can typically, but not exclusively, be selected as: 0.38–0.45% (e.g., 0.40%, 0.42%, 0.44%); the Si content can typically, but not exclusively, be selected as: 0.17–0.37% (e.g., 0.20%, 0.22%, 0.24%, 0.26%, 0.28%, 0.30%, 0.32%, 0.34%, 0.36%); the Mn content can typically, but not exclusively, be selected as: 0.50–0.80% (e.g., 0.55%, 0.60%, 0.65%, 0.70%, 0.75%); and the S content can typically, but not exclusively, be selected as: ≤0.035% (e.g., 0.030%, 0.020%, 0.010%, 0.005%, 0.035%). P can typically, but not limited to, be ≤0.035% (e.g., 0.030%, 0.020%, 0.010%, 0.005%, 0), Cr can typically, but not limited to, be 0.90–1.20% (e.g., 0.95%, 1.00%, 1.05%, 1.10%, 1.15%), Mo can typically, but not limited to, be 0.15–0.25% (e.g., 0.18%, 0.20%, 0.22%, 0.24%), Ni can typically, but not limited to, be 0.02–0.05% (e.g., 0.03%, 0.04%), Cu can typically, but not limited to, be ≤0.30% (e.g., 0.20%, 0.10%, 0.05%, 0), with the remainder being Fe and unavoidable impurities.
[0033] According to a second aspect of the present invention, the present invention provides a method for preparing the 12.9 grade wind turbine bolt material described in the first aspect, wherein round steel material prepared by converter, LF refining, RH vacuum degassing, continuous casting and rolling processes is subjected to quenching and tempering heat treatment. The rolling process employs controlled rolling and controlled cooling, and the final rolling temperature during controlled rolling is not less than 810℃ (e.g., 812℃, 815℃, 817℃, 820℃, 822℃). The controlled cooling rates are 0.5-0.8℃ / s (e.g., 0.6℃ / s, 0.62℃ / s, 0.64℃ / s, 0.66℃ / s, 0.68℃ / s, 0.7℃ / s, 0.72℃ / s, 0.74℃ / s, 0.76℃ / s, 0.78℃ / s).
[0034] As an optional embodiment of the preparation method of the 12.9 grade wind power bolt material of the present invention, the final rolling temperature is 810-840℃ (812℃, 815℃, 817℃, 820℃, 822℃, 825℃, 827℃, 830℃, 832℃, 835℃, 837℃).
[0035] In the preparation method of this invention, a uniform and stable ferrite (F) and pearlite (P) microstructure is obtained through controlled rolling and cooling during the rolling process, which is more conducive to improving the performance of subsequent quenching and tempering heat treatment. Conventional rolling and air cooling processes, on the other hand, result in bainitic microstructure, an unstable microstructure. Specifically, the final rolling temperature is controlled at no less than 810℃, and can be controlled within the range of 810-840℃. This is because if the temperature is too low, the deformation resistance is too high, which can easily damage the equipment; while the temperature should not be too high, as this not only increases energy consumption but also leads to a significant grain size increase trend, easily producing coarse grains. The cooling rate is controlled at 0.5-0.8℃ / s to ensure slow cooling, providing sufficient favorable time for the formation of ferrite (F) and pearlite (P).
[0036] As an optional embodiment of the preparation method of the 12.9 grade wind power bolt material of the present invention, the final rolling temperature is controlled by water cooling.
[0037] And / or, the cooling rate is controlled by using an insulation cover during controlled cooling.
[0038] In this invention, the cooling rate can be controlled by using an insulation cover or by other methods that can achieve a slow cooling effect.
[0039] As an optional embodiment of the preparation method of the 12.9 grade wind turbine bolt material of the present invention, the continuous casting adopts a light reduction technique.
[0040] In the above technical solution, a light reduction technique can be used during continuous casting to improve the density of the center of the continuously cast billet and improve the quality of the core material. This light reduction technique is a process where, during the continuous casting steelmaking process, when liquid core straightening is used for straightening the continuously cast billet, a small pressure is applied to the billet with a liquid core to slightly compress it in order to obtain a defect-free billet. Specifically, to reduce center segregation, the light reduction technique can be applied to the center segregation section (the final stage of billet solidification) during continuous casting. That is, at the point where it is almost completely solidified, the billet is slightly reduced (e.g., 6-8 mm) to prevent center segregation from severely affecting the internal quality of the billet. This is because center segregation is caused by the inward-growing solidification front forming a "bridge" that blocks the downward transport of molten steel. The solidification and cooling contraction causes the solidification shrinkage force to draw in the S and P-rich liquid between the surrounding dendrites, resulting in center segregation.
[0041] As an optional embodiment of the preparation method of the 12.9 grade wind power bolt material of the present invention, the temperature of the continuous casting billet before rolling is 1180~1220℃ (e.g. 1185℃, 1190℃, 1195℃, 1200℃, 1205℃, 1210℃, 1215℃).
[0042] As an optional embodiment of the preparation method of the 12.9 grade wind power bolt material of the present invention, the quenching adopts a quenching temperature of not less than 880℃ (e.g., 882℃, 884℃, 886℃, 888℃, 890℃, 892℃, 894℃, 896℃, 898℃, 900℃) and a water cooling process.
[0043] And / or, the tempering adopts a tempering temperature not exceeding 630°C (e.g., 610°C, 615°C, 620°C, 625°C, 630°C) and a water cooling process.
[0044] As an optional embodiment of the preparation method of the 12.9 grade wind power bolt material of the present invention, the quenching temperature is 880-900℃ (e.g., 882℃, 884℃, 826℃, 828℃, 890℃, 892℃, 894℃, 896℃, 898℃);
[0045] And / or, the tempering temperature is 570-630°C (e.g., 575°C, 580°C, 585°C, 590°C, 595°C, 600°C, 605°C, 610°C, 615°C, 620°C, 625°C).
[0046] As an optional embodiment of the preparation method of the 12.9 grade wind turbine bolt material of the present invention, the quenching temperature is 880℃, and the tempering temperature is 570-630℃ (e.g., 575℃, 580℃, 585℃, 590℃, 595℃, 600℃, 605℃, 610℃, 615℃, 620℃, 625℃); further, the quenching temperature is 880℃, and the tempering temperature is 630℃;
[0047] And / or, the quenching temperature is 900℃, and the tempering temperature is 600-630℃ (e.g., 602℃, 604℃, 606℃, 608℃, 610℃, 612℃, 614℃, 616℃, 618℃, 620℃, 622℃, 624℃, 626℃, 628℃).
[0048] In the preparation method of this invention, materials meeting the 12.9 grade performance requirements can be obtained through quenching and tempering treatment. In particular, quenching is carried out at a quenching temperature of not less than 880℃, and tempering is carried out at a tempering temperature of not more than 630℃, which can produce bolt materials larger than φ40mm, such as φ72mm. Through a large number of different quenching + tempering heat treatment experiments, the inventors obtained the optimal heat treatment process that meets the 12.9 grade performance of bolt materials and the large size requirements of M42-M72, namely, quenching temperature of 880℃ + tempering temperature of 630℃.
[0049] According to a third aspect of the present invention, the present invention provides the application of the 12.9 grade wind turbine bolt material described in the first aspect or the 12.9 grade wind turbine bolt material prepared by the preparation method of the second aspect, wherein the 12.9 grade wind turbine bolt material is applied to the preparation of M42-M72 specification, 12.9 grade high strength wind turbine bolts.
[0050] The present invention will now be described in further detail with reference to specific embodiments and comparative examples.
[0051] Examples 1-8 and Comparative Examples 1-8
[0052] The process of using a 120t top and bottom combined blowing converter → LF refining → RH vacuum degassing → continuous casting of 410mm×530mm → continuous rolling mill is adopted to produce φ72mm round steel (YGFD12.9, i.e. 12.9 grade M72 large-size wind power bolt material (42CrMoVNb)).
[0053] The composition of the round steel, by mass percentage, is: w[C]: 0.42%, w[Si]: 0.27%, w[Mn]: 0.55%, w[P]: 0.007%, w[S]: 0.002%, w[Cr]: 1.10%, w[Mo]: 0.25%, w[Cu]: 0.02%, w[Ni]: 0.36%, w[V]: 0.12%, w[Nb]: 0.025%, w[Al]: 0.024%, with the remainder being Fe and unavoidable impurities.
[0054] The continuous casting process uses a 410mm×530mm continuous casting machine, and a light reduction technique (reduction of 7mm) is used at the end of the solidification stage of the billet.
[0055] Before rolling, a walking beam furnace is used for heating. To ensure uniform heating of the billet, the total heating time is controlled at about 10 hours, of which the high-temperature holding temperature is controlled at 1180-1220℃ and the high-temperature holding time is 120 minutes. A controlled rolling and controlled cooling process is adopted. During rolling, the final rolling temperature is controlled by water cooling. The final rolling temperature is 830℃. A heat preservation cover is used to slowly cool the billet at a cooling rate of 0.5-0.8℃ / s to obtain a stable ferrite F+ pearlite P structure.
[0056] During the quenching and tempering process, different quenching temperatures and water cooling treatments were used, as well as different tempering temperatures and water cooling treatments. The specific temperatures for the quenching and tempering treatments in Examples 1-8 and Comparative Examples 1-8 are shown in Table 1. Referring to GB / T228.1-2021 Metallic materials—Tensive testing—Part 1: Tests at room temperature, and also referring to GB / T229-2020 Metallic materials—Charpy impact test, the mechanical properties (tensile strength (Rm), yield strength (Rp)) of the obtained materials were evaluated. 0.2 The following parameters were tested: elongation at break (A), reduction of area (Z), and impact energy at -40℃ (KV2). The test results are shown in Table 1.
[0057] Table 1
[0058]
[0059] The quenching and tempering heat treatment tests show that, under the same tempering temperature, quenching temperatures of 880℃ and 900℃ have little effect on strength. Under the same quenching temperature, the tensile strength and yield strength of YGFD12.9 steel gradually decrease with increasing tempering temperature. When the tempering temperature exceeds approximately 600℃, both tensile strength and yield strength decrease sharply. Different tempering temperatures have a significant impact on impact toughness. The impact value increases significantly when the tempering temperature increases from approximately 600℃ to 610℃. When the tempering temperature is below approximately 600℃, the tensile strength does not decrease linearly with increasing tempering temperature, mainly due to the dispersed precipitation of Mo and V alloy carbides, resulting in secondary hardening. The sharp decrease in strength after the tempering temperature exceeds 610℃ is due to over-aging, where alloy carbides aggregate and grow, weakening the resistance to dislocation movement. The quenching and tempering process selected is 880℃ quenching + 630℃ tempering, which yields mechanical properties of 1282MPa tensile strength, 1230MPa yield strength, 57% reduction of area, and 62J impact energy at -40℃. 880℃ quenching + 630℃ tempering is the optimal quenching and tempering process for YGFD12.9 steel to meet the performance requirements of 12.9 grade, M42-M72 large-size wind power fasteners.
[0060] This production of φ72mm YGFD12.9 steel, by mass percentage, has the following composition: C: 0.42%, Si: 0.27%, Mn: 0.55%, P: 0.007%, S: 0.002%, Cr: 1.10%, Mo: 0.25%, Cu: 0.02%, Ni: 0.36%, V: 0.12%, Nb: 0.025%, Al: 0.024%, with the remainder being Fe and unavoidable impurities. The tempering process, using 880℃ quenching followed by 630℃ tempering, successfully yielded material meeting the performance requirements of grade 12.9 wind turbine bolts. The metallographic structure of the rolled material is shown below. Figure 1 , 2 As shown, from Figure 1 It can be seen that the controlled rolling and cooling process yielded a uniform and stable microstructure of ferrite (F) and pearlite (P); from Figure 2 It can be seen that after quenching at 880℃ and tempering at 630℃, the resulting material has a tempered sorbite microstructure that is uniform. Furthermore, in Example 5, a light reduction technique was used during continuous casting, and the low-magnification microstructure of the rolled material is shown below. Figure 3 As shown, from Figure 3 It is evident that the core structure of the material obtained after rolling is dense.
[0061] Example 9
[0062] The only difference between this embodiment and embodiment 5 is that the light reduction technique was not used in the continuous casting process; all other settings are the same as in embodiment 5.
[0063] This embodiment does not employ a light reduction technique; the low-magnification microstructure of the rolled material is shown below. Figure 4 As shown, from Figure 4 and Figure 3 The comparison shows that Figure 4 The core structure of the material obtained after rolling is not as good as Figure 3 The core structure is dense, which shows that the light reduction technology can improve the density of the center of the continuously cast billet, improve the core quality of the material, and ultimately improve the mechanical properties of the material to a certain extent.
[0064] Comparative Example 9
[0065] The only difference between this comparative example and Example 5 is that the round steel composition is: Mn 0.6%, Cr 0.9%, and Mo 0.15%. All other components and preparation methods are the same as in Example 5. As shown in Table 1, the φ72mm YGFD12.9 round steel produced in this comparative example fails the impact energy test. This is likely due to the influence of the Mn, Cr, and Mo contents on the material's hardenability.
[0066] Comparative Example 10
[0067] The only difference between this comparative example and Example 5 is that the round steel does not contain V or Nb; the other components and preparation are the same as in Example 5.
[0068] As can be seen from Table 1, the impact energy of the φ72mm YGFD12.9 round steel produced in this comparative example is unqualified. This should be because the absence of V and Nb results in a less refined grain size than in Example 5, which ultimately affects the impact energy and leads to the failure of the impact energy test.
[0069] Comparative Example 11
[0070] The only difference between this comparative example and Example 5 is that the round steel does not contain Ni; the other components and preparation are the same as in Example 5.
[0071] Table 1 shows the tensile strength (Rm) and yield strength (Rp) of the φ72mm YGFD12.9 round steel produced in this comparative example. 0.2 Both the impact energy and the performance are substandard, and the performance cannot meet the requirements of grade 12.9 fasteners.
[0072] Comparative Example 12
[0073] The only difference between this comparative example and Example 5 is that the cooling rate during controlled cooling during rolling is 1.0℃ / s. After controlled cooling, a bainitic structure was obtained, which is an unstable structure. Based on this, the optimal tempering process of 880℃ quenching + 630℃ tempering was performed. The resulting material properties barely meet the requirements for grade 12.9 fasteners, but the tensile strength (Rm) and yield strength (Rp) are significantly lower. 0.2 In particular, the impact energy is not as good as that of Example 5.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a grade 12.9 wind turbine bolt material, characterized in that, The φ72mm round steel YGFD12.9 is produced using a 120t top and bottom blowing converter, LF refining, RH vacuum degassing, continuous casting, and continuous rolling mill rolling process; the round steel undergoes quenching, water cooling, tempering, and water cooling heat treatment. The composition of the round steel, by mass percentage, is: C: 0.42%, Si: 0.27%, Mn: 0.55%, P: 0.007%, S: 0.002%, Cr: 1.10%, Mo: 0.25%, Cu: 0.02%, Ni: 0.36%, V: 0.12%, Nb: 0.025%, Al: 0.024%, with the remainder being Fe and unavoidable impurities; The continuous casting process uses a 410mm×530mm continuous casting machine, and a light reduction technique is used at the end of the solidification of the billet, with a reduction of 7mm. Before rolling, a walking beam furnace is used for heating, with a total heating time controlled at 10 hours. The high-temperature holding temperature is controlled at 1180~1220℃ for 120 minutes. The rolling process adopts a controlled rolling and cooling process. During rolling, the final rolling temperature is controlled by water cooling, with a final rolling temperature of 830℃. A heat preservation cover is used to slowly cool the rolling process at a cooling rate of 0.5-0.8℃ / s. During the quenching and tempering process, the quenching temperature is 880℃ and the tempering temperature is 630℃.
2. The application of a grade 12.9 wind turbine bolt material prepared by the method described in claim 1, characterized in that, The 12.9 grade wind turbine bolt material is used in the preparation of M42-M72 specification, 12.9 grade high strength wind turbine bolts.
Citation Information
Patent Citations
High-strength steel with delayed fracture resistance and preparation method of high-strength steel
CN109161794A
Production method of high-strength steel for wind power fasteners
CN119913414A